2004
DOI: 10.1164/rccm.200403-307oc
|View full text |Cite
|
Sign up to set email alerts
|

T Cell–Based Tracking of Multidrug Resistant Tuberculosis Infection after Brief Exposure

Abstract: Molecular epidemiology indicates significant transmission of Mycobacterium tuberculosis after casual contact with infectious tuberculosis cases. We investigated M. tuberculosis transmission after brief exposure using a T cell-based assay, the enzyme-linked-immunospot (ELISPOT) for IFN-gamma. After childbirth, a mother was diagnosed with sputum smear-positive multidrug-resistant tuberculosis. Forty-one neonates and 47 adults were present during her admission on the maternity unit; 11 weeks later, all underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 36 publications
5
109
0
6
Order By: Relevance
“…The current authors' tentative conclusions are supported by the substantial body of literature demonstrating that the T-SPOT.TB TM test result correlates more closely with exposure [10][11][12][13][14], is more sensitive than the TST [7,[15][16][17][18] and is not prone to cross-reaction to BCG and most nontuberculous mycobacteria [11,[19][20].…”
Section: Discussionsupporting
confidence: 55%
“…The current authors' tentative conclusions are supported by the substantial body of literature demonstrating that the T-SPOT.TB TM test result correlates more closely with exposure [10][11][12][13][14], is more sensitive than the TST [7,[15][16][17][18] and is not prone to cross-reaction to BCG and most nontuberculous mycobacteria [11,[19][20].…”
Section: Discussionsupporting
confidence: 55%
“…18,68,86 The ELISPOT, which is commonly used in Europe, has been approved by the FDA in the United States in July 2008.…”
Section: Elispot (Available In the Market As T-spottb ® Oxfordmentioning
confidence: 99%
“…Table 1 shows a comparison between the TST and the IGRAs. Richeldi et al 18 commented that the fact that The literature has shown that undetermined results were found in up to 11% of the patients tested with the QFT-G, and this finding must be associated with the small number of immunosuppressed patients included in these studies. [98][99][100] Ferrara et al 79 found high rate of undetermined results Other studies have shown that the prevalence of positive ELISPOT results was higher than that found using the TST, mainly in immunosuppressed patients.…”
Section: Elispot (Available In the Market As T-spottb ® Oxfordmentioning
confidence: 99%
See 2 more Smart Citations